Wafer-sized multifunctional polyimine-based two-dimensional conjugated polymers with high mechanical stiffness - Sahabudeen, Hafeesudeen; Qi, Haoyuan; Glatz, Bernhard Alexander; Tranca, Diana; Dong, Renhao; Hou, Yang; Zhang, Tao; Kuttner, Christian; Lehnert, Tibor; Seifert, Gotthard; Kaiser, Ute; Fery, Andreas; et al. (Nature Communications, 2016)
One of the key challenges in two-dimensional (2D) materials is to go beyond graphene, a prototype 2D polymer (2DP), and to synthesize its organic analogues with structural control at the atomic- or molecular-level. Here we show the successful preparation of porphyrin-containing monolayer and multilayer 2DPs through Schiff-base polycondensation reaction at an air-water and liquid-liquid interface, respectively. Both the monolayer and multilayer 2DPs have crystalline structures as indicated by selected area electron diffraction. The monolayer 2DP has a thickness of∼0.7 nm with a lateral size of 4-inch wafer, and it has a Young's modulus of 267±30 GPa. Notably, the monolayer 2DP functions as an active semiconducting layer in a thin film transistor, while the multilayer 2DP from cobalt-porphyrin monomer efficiently catalyses hydrogen generation from water. This work presents an advance in the synthesis of novel 2D materials for electronics and energy-related applications.
CRIS-Team Scopus Importer:2023-03-20